Standardization of glycerine preservation for ornamental foliage of different species suitable for value addition - SINGH, BABITA; JAIN, RITU; SINDHU, S S; KUMAR, PRABHAT; YADAV, HARENDRA; KUMAR, RAMAN (The Indian Journal of Agricultural Sciences, 2018)
Studies were carried out in the Division of Floriculture and Landscaping, ICAR-IARI New Delhi during 2016-17 to standardize the glycerine preservation technology for foliage of silver oak, cordyline, asparagus and fern under laboratory conditions. The foliage was subjected for glycerinization by immersing and uptake methods with different combinations of glycerine and water. Observations were made for moisture loss (%), time taken for drying and sensory parameters like texture, shape retention, brittleness, overall acceptance of the cut foliages etc. and were subjected to analysis of variance. In case of silver oak treating the foliage with 1:3 ratio of glycerine and water found better for minimum moisture loss (%) while 1:2 ratio of glycerine and water was suitable for minimum days taken for drying in both the methods i.e. full dip and uptake and for most the qualitative parameters 1:3 ratio of glycerine and water were recorded better score in silver oak. For asparagus 1:3 ratio of glycerine and water with full dip method found most suitable for quantitative and the qualitative parameters were also found best in 1:3 ratio of glycerine and water but in both the methods i.e. full dip and uptake. In case of cordyline 1:3 ratio of glycerine and water found suitable for minimum moisture loss (%) and uptake method with1:3 ratio of glycerine and water recorded minimum days taken for drying. Sensory parameters revealed similar finding as quantitative parameters. Treating the foliage of fern in 1:3 ratio of glycerine and water with full dip method were found better for quantitative parameters studied as well as for most of the qualitative parameters also.